Chronic conditions, multimorbidity, and quality of life among patients attending monk healers and primary care clinics in Thailand - Supa Pengpid (2022)
Background: The study aimed to assess chronic diseases, multimorbidity, and QoL among patients attending two different treatment settings in Thailand. Methods: In all, 1409 attendees of three monk healer or three health centres were assessed with self-reported measures on chronic conditions and Quality of Life (QoL). Results: Results indicate that the most common chronic conditions were common mental disorder (25.2%), followed by hypertension (22.8%), high blood cholesterol (18.0%), fatigue disorder (14.4%), diabetes (14.0%), migraine headaches (13.7%), sleeping problem (12.2%), and ulcer (11.0%). In all, 40.6% had multimorbidity (two or more chronic conditions) (42.4% in the monk healer and 38.9% in the primary care setting). In ANCOVA analysis, adjusted for sex, age, employment status, marital status, education, economic status, comorbidity, and health care setting, the poorest overall QoL was found among clients with common mental disorders (58.5 mean score), followed by emphysema or asthma (60.2), sleeping problem (61.5), migraine headaches (62.7), fatigue disorder (63.3), substance use disorder (63.6) and ulcer (64.3). The overall QoL was poorer among monk healer clients (66.5) than primary care patients (68.8). In adjusted logistical regression analysis, being a monk healer attendee, older age (55–93 years), and high debt were positively, and being employed and better overall quality of life were negatively associated with multimorbidity, overall, for the monk healer and primary care setting. In adjusted linear regression analyses, primary health care attenders, older age, were employed and post-secondary education increased the odds of better overall QoL. Conclusion: Multimorbidity was higher among clients attending monk healers than those attending primary care facilities and QoL was poorer among clients seeking care from monk healers than those attending primary care. High multimorbidity was found and major chronic conditions were found to have poor QoL. Determinants of multimorbidity and QoL in two different treatment settings provide information to improve the management of chronic conditions.